The effects of management practices on effective tax rates: Evidence from Ecuador - Javier Beverinotti; Gustavo Canavire-Bacarreza; María Cecilia Deza; Lyliana E. Gayoso de Ervin (Inter-American Development Bank (IDB), 2021)
This paper examines the effects of management practices on effective tax rates (ETR) in a sample of medium and large manufacturing firms in Ecuador. We use a novel data set on management practice scores matched with administrative tax data from the Superintendence of Companies and the Internal Revenue Services of Ecuador based on firms' tax filings. We find that better management practices are positively associated with effective tax rates, defined as the share of tax obligations to profits. This result is robust under various specifications controlling for different covariates, and to different measures of effective tax rates. Furthermore, our findings indicate that the use of fiscal incentives is positively associated with higher effective tax rates. However, firms that use fiscal incentives are able to fatten or reduce their effective tax rates as management practices improved. Overall, our findings suggest that government-sponsored policies that seek to promote better management practices may be self-sustained, if the additional tax revenue expected from better management practices through higher profits is able to cover the cost of the programs.
Keywords: D22; H2; L2; M2; 330; management practices; tax obligations; tax incentives; productivity